Iridium-catalyzed asymmetric allylic substitutions with bulky amines/oxidative double bond cleavage: entry into the Reetz synthesis of amino alcohols - Seehafer, Kai; Malakar, Chandi Charan; Bender, Markus; Qu, Jianping; Liang, Chen; Helmchen, Günter (European journal of organic chemistry, 2016)
Branched allylic amines were prepared by Ir-catalyzed enantioselective allylic aminations with the bulky N-nucleophiles HN(Boc)2 and HNBn2. The products were transformed into N-protected amino aldehydes, which were either reduced or coupled diastereoselectively with organometallic compounds to give vicinal amino alcohols. A formal synthesis of the neurokinin receptor antagonist (+)-L-733060 was carried out as an application.